Postoperative outcomes after total sevoflurane inhalation sedation using a disposable delivery system (Sedaconda-ACD) in cardiac surgery - Labaste, François; Cauquil, Paul; Lestarquit, Magda; Sanchez-Verlaan, Pascale; Aljuayli, Abdulrahman; Marcheix, Bertrand; Geeraerts, Thomas; Ferre, Fabrice; Vardon-Bounes, Fanny; Minville, Vincent (Frontiers in Medicine, 2024)
Introduction The COVID-19 pandemic prompted our team to develop new solutions for performing cardiac surgery without intravenous anesthetics due to a shortage of these drugs. We utilized an anesthetic conserving device (Sedaconda-ACD) to administer total inhaled anesthesia because specific vaporizers were unavailable for administering inhaled agents during cardiopulmonary bypass (CPB) in our center. We documented our experience and postoperative cardiovascular outcomes. The primary outcome was the peak level of troponin, with secondary outcomes encompassing other cardiovascular complications. Material and methods A single-center retrospective study was conducted. We performed a multivariate analysis with a propensity score. This investigation took place at a large university referral center. Participants Adult patients (age ≥ 18) who underwent elective cardiac surgery with CPB between June 2020 to March 2021. Intervention During the inclusion period, two anesthesia protocols for the maintenance of anesthesia coexisted—total inhaled anesthesia with Sedaconda-ACD and our classic protocol with intravenous drugs during and after CPB. Primary endpoint Troponin peak level recorded after surgery (highest level recorded within 48 h following the surgery). Results Out of the 654 included patients, 454 were analyzed after matching (intravenous group = 297 and inhaled group = 157). No significant difference was found between the groups in postoperative troponin peak levels (723 ng/l vs. 993 ng/l–p = 0.2). Total inhaled anesthesia was associated with a decreased requirement for inotropic medications (OR = 0.53, 95% CI 0.29–0.99, p = 0.04). Conclusion In our cohort, the Sedaconda-ACD device enabled us to achieve anesthesia without intravenous agents, and we did not observe any increase in postoperative complications. Total inhaled anesthesia with sevoflurane was not associated with a lower incidence of myocardial injury assessed by the postoperative troponin peak level. However, in our cohort, the use of inotropic drugs was lower.